Description of a polyvalent conjugate and a new serogroup of Bacteroides melaninogenicus by fluorescent antibody staining. - Lambe, D W (1976)
A polyvalent conjugate (fluorescein isothiocyanate-labeled antibody reagent) containing serogroups A, B, and C conjugates was prepared. This polyvalent conjugate gave a positive fluorescent antibody (FA) stain with 49 stains of Bacteroides melaninogenicus representing serogroups A, B, and C. When additional strains (92 strains) of the three subspecies of B. melaninogenicus were examined by the FA stain, with A, B, and C, and polyvalent conjugates, nine strains of B. melaninogenicus subsp. intermedius failed to give a positive stain with any conjugate. Therefore, an FA conjugate was prepared with the antiserum to one of these strains (532-70A); all nine strains stained positively with this conjugate. These nine strains were biochemically characteristic of B. melaninogenicus subsp. intermedius; thus, these strains were designated as a new serogroup, serogroup C-1. A new polyvalent conjugate containing serogroups A, B, C, and C-1 was prepared. This polyvalent conjugate stained positively with 23 representative strains from serogroups A, B, C, and C-1. The new conjugates failed to stain positively with other anaerobes and aerobes tested. The four individual conjugates, as well as the polyvalent conjugate, may be used for a more rapid identification of B. melaninogenicus than is possible by biochemical testing.